2020
DOI: 10.1177/2050303220952868
|View full text |Cite
|
Sign up to set email alerts
|

Postfeminist, engaged and resistant: Evangelical male clergy attitudes towards gender and women’s ordination in the Church of England

Abstract: Despite the introduction of female bishops, women do not hold offices on equal terms with men in the Church of England, where conservative evangelical male clergy often reject the validity of women’s ordination. This article explores the gender values of such clergy, investigating how they are expressed and the factors that shape them. Data is drawn from semi-structured interviews and is interpreted with thematic narrative analysis. The themes were analyzed with theories on postfeminism, engaged orthodoxy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Such lines of enquiry could focus on the historic context of that culture and the impact this has on unintended institutional work. It is unlikely to be a coincidence that the charismatic evangelicals interviewed inhabit a tradition that has historically been more affirming of women's ministry and reported behaviors that can foster greater levels of gender equality, particularly given that the history of a religious tradition shapes it in the present (see Fry, 2019a, 2021; Vasey‐Saunders, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such lines of enquiry could focus on the historic context of that culture and the impact this has on unintended institutional work. It is unlikely to be a coincidence that the charismatic evangelicals interviewed inhabit a tradition that has historically been more affirming of women's ministry and reported behaviors that can foster greater levels of gender equality, particularly given that the history of a religious tradition shapes it in the present (see Fry, 2019a, 2021; Vasey‐Saunders, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, Bagilhole (2006) concluded that female clergy in the CofE are not faced with a glass ceiling so much as a “lead roof” (p. 109), or even—in the words of Peyton and Gatrell (2013)—a “stained glass ceiling” (p. 16; also see Gatrell & Peyton, 2019). Most recently, I have shown that belief in gender differentiation—that men and women should occupy distinct spheres—amongst conservative evangelical clergy limits the possibility of gender equality within the CofE (Fry, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Broadly speaking, the Anglo-Catholic tradition and the conservative evangelical tradition historically rejected the ordination of women, whereas the charismatic evangelical tradition historically encouraged women's ministry (Fry 2021a). Even in contexts where the Anglican Church has admitted women into leadership at all levels, evidence of gender inequality remains; within the Church of England, it is historic and ongoing, including in the governing structures of the church, selection processes for clergy and pay rates (Fry 2019(Fry , 2021a(Fry , 2021bGreene and Robbins 2015). In an empirical review of gender roles and church tradition in the Church of England, Village (2012) found those with a broad church identity tended to hold views more closely aligned with wider society on matters such as women's ordination, divorce, and remarriage, in contrast to more conservative views held by conservative Anglo-Catholics or evangelicals.…”
Section: The Anglican Churchmentioning
confidence: 99%